A política antipobreza no governo Lula: uma análise do discurso - Franco, Leila Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This study aims to show the speech of and on the Allowance Family Program (AFP), inserted in Anti-poverty Income Transfer Policy, under Lula. The theoretical orientation is the Discourse Analysis of French Line in Pecheux (1997), Orlandi (2001a, 2001b). It is also based on questions of political discourse in Pecheux (1981, 2008), Orlandi (2001b), Zoppi-Fontana (1997), Courtine (1990), Lagazzy-Rodrigues (1998) and journalistic discourse in Mariani (1998), among others. The corpus includes: Law nr. 10.836, of January 9, 2004, and Decree nr. 5.209, of September 17, 2004, which regulates the Allowance Family Program; interviews with ten (10) beneficiaries living in Uberaba, state of Minas Gerais (Brazil), benefited by the Income Transfer Allowance Family Program; 60 journalistic articles, written from January 2003 to January 2010 in three newspapers – from Folha de S. Paulo, Estado de Minas and O Globo newspapers - 20 of each one. By showing the discursive function of the sequences, we found that the discursive place in the three anchors of analysis comes from a Welfare State. By the State, the guarantor, the provider, in order to give income (basic benefit, variable benefit) to all who need it – the beneficiaries, thence the condition needed/assisted by the State. By the beneficiaries, a subject-position of submission - by consensus - in relation to the way how the State individualizes them – the subject-position assisted/needy, the subject-position-State-Father/Protector/Provider; by the journalistic discourse which watches the State in order to point its emptying amid management problems, management, which disqualifies the political, reduced to welfare issues, political-party ones; by subject-position-State: submitted to God/religious/capitalist. Thus, the way the language was mobilized to produce meanings in socio-historical situation already marks a direction, and this is political

Este estudo objetiva mostrar o discurso do e sobre o Programa Bolsa Família (PBF), inserido na Política Antipobreza de Transferência de Renda, no governo Lula. A orientação teórica está na Análise do Discurso de Linha Francesa, em Pêcheux (1997), Orlandi (2001a, 2001b). Fundamenta-se, ainda, em questões acerca do discurso político em Pêcheux (1981, 2008), Orlandi (2001b), Zoppi-Fontana (1997), Courtine (1990), Lagazzy-Rodrigues (1998) e do discurso jornalístico, em Mariani (1998), entre outros. O corpus inclui: a Lei n 10.836, de 09 de janeiro de 2004, e o Decreto n 5.209, de 17 de setembro de 2004, o qual regulamenta o Programa Bolsa Família; entrevistas com 10 (dez) beneficiárias, residentes na cidade de Uberaba, Minas Gerais, beneficiadas pelo Programa de Transferência de Renda Bolsa Família; 60 artigos jornalísticos, veiculados no período de janeiro de 2003 a janeiro de 2010, em três jornais – Folha de S. Paulo, Estado de Minas, O Globo –, sendo 20 de cada jornal. Ao mostrar o funcionamento discursivo das sequências, verificamos que o lugar discursivo nas três ancoragens de análise é o do Estado assistencialista. Da parte do Estado, o garantidor, o provedor, no sentido de dar renda (benefício básico, benefício variável) a todos que dele necessitam – os beneficiários; daí a condição de necessitado/assistido pelo Estado. Da parte das beneficiárias, uma posição -sujeito de submissão - do consenso-, em relação ao modo pelo qual o Estado as individualiza - da posição-sujeito assistida/necessitada, da posição-sujeito-Estado-Pai/Protetor/Provedor; da parte da discursividade jornalística que espreita o Estado para apontar o seu esvaziamento em meio a problemas de gestão, gerenciamento, que desqualifica o político, reduzido a questões assistencialistas, político-partidárias; da posição sujeito-Estado: sujeito a Deus/religioso/ capitalista. Logo, a forma como a língua foi mobilizada para produzir ...
Keywords: Linguística; Análise do discurso - Brasil; Ponto de vista (Literatura); Politicas publicas - Brasil; Discourse analysis